2020
DOI: 10.1016/s1473-3099(19)30649-8
|View full text |Cite
|
Sign up to set email alerts
|

Xpert MTB/RIF Ultra versus Xpert MTB/RIF for the diagnosis of tuberculous meningitis: a prospective, randomised, diagnostic accuracy study

Abstract: Background Xpert MTB/RIF Ultra (Xpert Ultra) might have higher sensitivity than its predecessor, Xpert MTB/RIF (Xpert), but its role in tuberculous meningitis diagnosis is uncertain. We aimed to compare Xpert Ultra with Xpert for the diagnosis of tuberculous meningitis in HIV-uninfected and HIV-infected adults. Methods In this prospective, randomised, diagnostic accuracy study, adults (≥16 years) with suspected tuberculous meningitis from a single centre in Vietnam were randomly assigned to cerebrospinal fluid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
72
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(100 citation statements)
references
References 21 publications
7
72
0
2
Order By: Relevance
“…Several studies have been published on the diagnostic accuracy of Ultra in extrapulmonary specimens 11,14,15,[17][18][19][20][21][22][23][24][25]28,29 . Most of the studies were performed in TB endemic settings 14,17,[19][20][21][22][23][24][25]28,29 , and only three studies have investigated Ultra test performance in low TB prevalence settings 11,15,18 . However, two of these studies were retrospective and performed on selected sample material.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have been published on the diagnostic accuracy of Ultra in extrapulmonary specimens 11,14,15,[17][18][19][20][21][22][23][24][25]28,29 . Most of the studies were performed in TB endemic settings 14,17,[19][20][21][22][23][24][25]28,29 , and only three studies have investigated Ultra test performance in low TB prevalence settings 11,15,18 . However, two of these studies were retrospective and performed on selected sample material.…”
Section: Discussionmentioning
confidence: 99%
“…This is in concordance with the specificities (97-100%) found in other low TB prevalent settings where culture was used as reference standard 15,18 . However, in most of the studies that directly compare the performance of Xpert and Ultra, the specificity of Ultra is reduced compared to Xpert, both in extrapulmonary specimens 14,19,20,22,29 and sputum 9,10,12,13 . In low TB prevalent settings, even a small reduction in specificity could lead to unacceptable high rates of false positive cases, emphasizing that Ultra should be performed on selected samples with a high pre-test probability of TB disease.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TB/RIF Ultra is an advancement in the technique of Xpert with the addition of two different amplification targets. In a study by Donovan et al, the sensitivities of Xpert MTB/ RIF Ultra and Xpert MTB/RIF was 38.9 and 22.9 % in HIV negative tuberculous meningitis [32]. In a study by Yan et al, the sensitivity of metagenomic next-generation sequencing in the diagnosis of TBM was 84%, compared to 24.4 and 40 % with Mycobacterium PCR and Xpert MTB/RIF [33].…”
Section: Continuedmentioning
confidence: 99%
“…GeneXpert Ultra has 70% sensitivity versus clinical case definition and misses up to 30% of cases [5]. However, a recent study from Donovan et al reported that GeneXpert Ultra was not superior to GeneXpert for TBM diagnosis in both HIV-uninfected and HIV-infected adults [6]. This attracted our interest to validate the diagnostic performance of GeneXpert for the diagnosis of TBM by using Mycobacterial Growth Indicator Tube (MGIT 960) as a gold standard.…”
Section: Introductionmentioning
confidence: 99%